MultiMedia modeling. 23rd International Conference, MMM 2017, Reykjavik, Iceland, January 4-6, 2017, Proceedings /: 23rd International Conference, MMM 2017, Reykjavik, Iceland, January 4-6, 2017, Proceedings. Part II : (2017) - Unknown
No abstract available